Multilocus sequence typing (MLST) analysis of Propionibacterium acnes isolates from radical prostatectomy specimens - Mak, Tim N.; Yu, Shu-Han; De Marzo, Angelo M.; Brüggemann, Holger; Sfanos, Karen S. (The Prostate, 2013)
BACKGROUND Inflammation is commonly observed in radical prostatectomy specimens, and evidence suggests that inflammation may contribute to prostate carcinogenesis. Multiple microorganisms have been implicated in serving as a stimulus for prostatic inflammation. The pro‐inflammatory anaerobe, Propionibacterium acnes, is ubiquitously found on human skin and is associated with the skin disease acne vulgaris. Recent studies have shown that P. acnes can be detected in prostatectomy specimens by bacterial culture or by culture‐independent molecular techniques. METHODS Radical prostatectomy tissue samples were obtained from 30 prostate cancer patients and subject to both aerobic and anaerobic culture. Cultured species were identified by 16S rDNA gene sequencing. Propionibacterium acnes isolates were typed using multilocus sequence typing (MLST). RESULTS Our study confirmed that P. acnes can be readily cultured from prostatectomy tissues (7 of 30 cases, 23%). In some cases, multiple isolates of P. acnes were cultured as well as other Propionibacterium species, such as P. granulosum and P. avidum. Overall, 9 of 30 cases (30%) were positive for Propionibacterium spp. MLST analyses identified eight different sequence types (STs) among prostate‐derived P. acnes isolates. These STs belong to two clonal complexes, namely CC36 (type I‐2) and CC53/60 (type II), or are CC53/60‐related singletons. CONCLUSIONS MLST typing results indicated that prostate‐derived P. acnes isolates do not fall within the typical skin/acne STs, but rather are characteristic of STs associated with opportunistic infections and/or urethral flora. The MLST typing results argue against the likelihood that prostatectomy‐derived P. acnes isolates represent contamination from skin flora. Prostate 73: 770–777, 2013. © 2012 Wiley Periodicals, Inc.